Regulation and resistance to HIV-Vpr induced apoptosis - Mishra, Sasmita (University of Ottawa (Canada), 2007)
Apoptosis of CD4+ T cells and their eventual depletion constitute a hallmark of HIV infection and disease progression. However, monocytes/macrophages unlike CD4+ T cells survive HIV replication and hence represent a major reservoir of virus. The mechanism underlying this resistance to HIV-mediated apoptosis in monocytic cells is not clear. It is believed that TNF-alpha which is produced during HIV infection may play a major role in inducing resistance in monocytes. In this study I investigated the molecular mechanisms involved in regulation of resistance to HIV-Vpr induced apoptosis in monocytic cells. LPS and LPS induced TNF-alpha are known to induce resistance to monocyte apoptosis. However, the molecular mechanism regulating this process is not known. cIAP2, one of the anti-apoptotic genes is known to be induced in monocytes in response to LPS. First of all, I demonstrated that LPS and TNF-alpha induced survival of human monocytic cells through the induction of the c-IAP2 gene. Further, I studied the involvement of MAPKs and PI3K signaling pathways in c-IAP2 induction by using specific pharmacological inhibitors. My results suggest that neither MAPKs nor PI3K is involved in c-IAP2 induction. Since calcium signaling pathway is considered to be one of the upstream signaling molecules in signaling cascade, I investigated its involvement in c-IAP2 induction in monocytic cell line. I showed that binding of LPS/TNF-alpha to their respective receptors induces calcium influx. Calcium is also known to activate calmodulin (CaM) which in turn activates various kinases and phosphatases. My results revealed that activation of CaM and CaM kinase II (CAMKII) is involved in c-IAP2 induction, whereas calcineurin, the protein phosphatase activated by CaM is not involved in this process. I have shown for the first time that LPS/TNF-alpha induced c-IAP2 and associated anti-apoptotic activity is regulated by CaM/CAMKII through the activation of NFkappaB. Since TNF-alpha is believed to be involved in inducing resistance to HIV induced apoptosis in monocytes, further I used Vpr, one of the HIV proteins to induce apoptosis in monocytes. My results showed that HIV-Vpr induces apoptosis in monocytes and pretreatment of cells with either LPS/TNF-alpha induces resistance to Vpr mediated apoptosis. To determine the molecular mechanisms involved in Vpr induced apoptosis, I used the C-terminal synthetic peptide (Vpr52-96) which mimics the whole Vpr protein for induction of apoptosis. I also used the N-terminal (Vpr1-45 aa) peptide as control. I demonstrated that both the C-terminal and N-terminal peptides phosphorylate all the three MAPKs such as p38, ERK, and JNK MAPK; however, only C-terminal (Vpr52-96) peptide induced apoptosis is regulated selectively by JNK MAPK. To determine the involvement of pro- and anti-apoptotic genes in Vpr induced apoptosis, RNAse protection assay was performed. My results revealed that in response to Vpr52-96, there was downregulation of Bc12, whereas other pro and anti-apoptotic genes of Bc12 family remained unchanged. I also demonstrated the involvement of c-IAP1, one of the inhibitor of apoptotic proteins (IAPs) in Vpr induced apoptosis. My results show that Vpr peptide-induced apoptosis is mediated by down regulation of anti-apoptosic Bc12 and c-IAP1 genes through JNK MAPK activation. Deregulation of the JNK pathway has been implicated in cancer and other diseases. Therefore, investigation of the molecular mechanisms that govern the role of the JNK pathway in apoptosis should provide insight into its biological functions and strategies to target this pathway for prevention and treatment of human diseases and cancer. Finally, I demonstrated that pretreatment of cells with LPS or TNF-alpha induced resistance to Vpr52-96 mediated apoptosis. My results suggest that LPS induced resistance is mediated by endogenous production of TNF-alpha in monocytes. I also demonstrated that LPS/TNF-alpha mediated resistance is regulated by induction of c-IAP2 through NFkappaB by activation of CAMKII. However, pretreatment with Vpr followed by LPS or TNF-alpha stimulation no longer gave protection to Vpr induced apoptosis. Vpr peptide also inhibited LPS/TNF-alpha-induced calcium influx, activation of CAMKII, and c-IAP2 induction. Taken together, my results suggest that the c-IAP2 gene plays a critical role in LPS and TNF-alpha-induced resistance to HIV-Vpr-mediated apoptosis in human monocytic cells. Since the calcium/CAMKII pathway is involved in LPS/TNF-alpha induced resistance to Vpr mediated apoptosis, strategies based on manipulation of these molecules, which would suppress c-IAP2 induction may be useful in clearing virus reservoirs in monocytes.
Keywords: Health Sciences, Immunology.